Penghasil Energi Listrik Menggunakan Piezoelectric yang Memanfaatkan Hukum Konversi Energi - Deva Naufal; Haula Syakira Alfisyahrin; Shiva Aulia Kharami; Febriza Melinda Tiara; Sherly Mutiara Riano; Nurhidayatulloh Nurhidayatulloh (LPPM Institut Pendidikan Nusantara Global, 2026)
This research aims to design and implement an innovative small-scale power generator prototype that utilizes wasted mechanical energy from daily human activities. The focus of this development is to convert foot pressure into sustainable alternative energy. Technically, this system adopts the concepts of electromagnetic induction and the piezoelectric effect, which can convert the kinetic energy of human body weight into electrical energy based on the principle of the law of conservation of energy, which states that energy cannot be destroyed but only converted from mechanical energy to electrical energy. The average voltage generated by a 45 kg person is 6,93 volts, capable of lighting an LED lamp for 0.5 seconds. This prototype is built using a series of piezoelectric sensors strategically configured under the foot platform. Because the energy output of piezoelectric components is alternating current (AC) with unstable fluctuations, the system is equipped with a bridge rectifier circuit to convert it to direct current (DC). The current is then stabilized and stored in an energy storage capacitor before being distributed to an electronic load. As a demonstration of the system's functionality, the collected energy is used to power an LED lamp. The results of this research are expected to serve as a reference in the development of energy harvesting technology that can be widely applied in public areas with high pedestrian traffic.